Pengaruh Alkalisasi Komposit Serat Kelapa-Poliester Terhadap Kekuatan Tarik - Maryanti, Budha; Sonief, Ahmad As'ad; Wahyudi, Slamet (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2011)
The purpose of this research is to analyze the effect of alkalization on the tensile strength and strain of coconut fiber composites with polyester matrix by varying the concentration of NaOH as follow 0%, 2%, 5% and 8%. Alkalization is one of modifications natural fibers to improve fiber-matrix compatibility.The method of this research used a hands lay-up method. As follow the 1st coconut fiber treated without alkalization or 0% alkalization and the 2nd coconut fiber immersed in alkaline solution (2%, 5% and 8% NaOH) for 1 hour. Then, each treatment specimen molded to composite according to standard tensile test ASTM D638 –I. Coconut fiber volume fraction 30% and 70% polyester, and arranged coconut fiber straightly. And used the matrix polyester resin type 157 BTQN with hardener MEKPO 1%.The results of this research showed that coconut fiber reinforced composites with NaOH concentrations of 0%, 2%, 5% and 8% respectively has a tensile strength that is 90,144 MPa, 93.75 MPa, 97,356 MPa and 94,151 MPa. The optimum concentration limit of 5% NaOH produced the highest tensile strength 97,356 MPa, while the composite of coconut fiber without alkalization has the lowest tensile strength 90,144 MPa. Keywords: coconut fiber-polyester composites, alkalization, tensile strength